Factors that Influence Impulse Buying: A Literature Review - Nida Hanifah; Susilaningsih; Muhammad Sabandi (PT ARRUS Intelektual Indonesia, 2024)
An individual's personality, way of thinking, social interactions, and response to situations play an important role in impulse buying behavior. This phenomenon is now common among consumers, who often initially have the goal of buying one item but are tempted to buy additional items that attract attention while at the market. This article reviews the impulse buying literature, the focus is on understanding the phenomenon and the factors that influence it in the purchasing context. The method used is Systematic Literature Reviews (SLR). ). The research results show several factors that influence consumer impulse buying behavior. Positive emotions, store atmosphere, and financial knowledge interact to influence impulse buying tendencies.